Clinical Effectiveness of Pit and Fissure Sealants Using Solvents for Improving Surface Wettability of Enamel: A Randomized Controlled Trial - Anshula N Deshpande; Pooja V Bane; Simron Baishya; Yash Shah; Sneha Dori (Contemporary Clinical Dentistry)
Background: Preventive dental procedures are cornerstones of caries management. Introduction: This research aims to analyze the clinical effectiveness of pit and fissure sealants when applied to etched enamel pretreated with solvents compared to the conventional etch and seal technique. Subjects and Methods: Children and adolescents with clinically healthy occlusal surfaces or noncavitated occlusal carious lesions on permanent first and/or second molars in all four quadrants were randomly allocated into four groups. A total population of 87 participants (348 teeth) were selected for the research based on the inclusion criteria. Following the enrollment, teeth were etched and sequentially assigned for application of Group 1 = Conventional Etch Seal (control group), Group 2 = isopropyl alcohol (IPA), Group 3 = acetone, and Group 4 = ethanol before sealant application. All participants were evaluated for marginal integrity, discoloration, and clinical retention of pit and fissure sealant after 6-month intervals and 12-month intervals using Feigal’s criteria. Results: At 6-month and 12-month intervals, the collected data were compiled and statistically analyzed using the Chi-square test of significance for marginal integrity between groups all four groups. The Wilcoxon rank test was assigned to assess the difference between parameters measured at 6 months and 12 months. A highly significant difference was found between the groups (P < 0.05) for marginal integrity and anatomic form at 6 months and 12 months when intergroup comparison was done using the Kruskal–Wallis test. Conclusion: Surfactants such as IPA and acetone can be adopted while choosing methods for the long-term clinical success of resin-based sealants for increasing wettability and penetration depth.